Impact of morphological features and chemical composition of tendon biomimetic scaffolds on immune recognition via Toll-like receptors - Gil-Cantero, Sara; Iorio, Francesco; Ünalan, Irem; Kurtuldu, Fatih; Künig, Sarojinidevi; Wenhardt, Claus; Pinnaro′, Veronica; Aigner-Radakovics, Katharina; Steinberger, Peter; Boccaccini, Aldo R.; Stöckl, Johannes (Biomaterials Science, 2024)
Tendinopathies are a major worldwide clinical problem. The development of tendon biomimetic scaffolds is considered a promising, therapeutic approach. However, to be clinically effective, scaffolds should avoid immunological recognition. It has been well described that scaffolds composed of aligned fibers lead to a better tenocyte differentiation, vitality, proliferation and motility. However, little has been studied regarding the impact of fiber spatial distribution on the recognition by immune cells. Additionally, it has been suggested that higher hydrophilicity would reduce their immune recognition. Herein, polycaprolactone (PCL)-hyaluronic acid (HA)-based electrospun scaffolds were generated with different fiber diameters (in the nano- and micro-scales) and orientations as well as different grades of wettability and the impact of these properties on immunological recognition has been assessed, by means of Toll-like receptor (TLR) reporter cells. Our results showed that TLR 2/1 and TLR 2/6 were not triggered by the scaffolds. In addition, the TLR 4 signalling pathway seems to be triggered to a greater extent by higher PCL and HA concentrations, but the alignment of the fibers prevents the triggering of this receptor. Taken together, TLR reporter cells were shown to be a useful and effective tool to study the potential of scaffolds to induce immune responses and the results obtained can be used to inform the design of fibrous scaffolds for tendon repair.
CRIS-Team Scopus Importer:2024-08-23